Fare ricerca sulla storia di Venezia oggi: il seminario Venice in Question - Valentina Dal Cin (Diciottesimo Secolo, 2022)
This review describes the topics covered during eleven meetings held from February 4 to June 17, 2021 within the “Venice in Question” seminar, coordinated by Daniele Dibello (Universiteit Gent) and organized by the Deputazione di Storia Patria per le Venezie, alongside other Venetian institutions. Presenting recent studies on Venetian history, the seminar involved Italian and international scholars, animating a dialogue between different historiographical approaches and traditions. While embracing a broad chronological span, from the Middle Ages to the early 19th century, the seminar pointed out aspects relevant to scholars of the 18th century.